Preemptive multimodal analgesia for gynecologic oncology patients undergoing laparotomy: a randomized controlled trial - Geng, Zhiyu; Wang, Bojie; Zhang, Yan; Yan, Xin; Hu, Jun; Cui, Ran; Song, Linlin (Frontiers in Medicine, 2024)
Purpose Gynecologic oncology laparotomy leads to severe postoperative pain. We aimed to evaluate the effects of preemptive multimodal analgesic regimen on postoperative opioid consumption for patients undergoing gynecologic oncology laparotomy. Methods In this prospective, randomized clinical trial, 80 female patients scheduled for gynecologic oncology laparotomy were randomized to receive preemptive multimodal analgesia consisted of transversus abdominis plane (TAP) block, cyclooxygenase−2 inhibitors, acetaminophen and intravenous morphine patient-controlled analgesia (PCA) (Study group) or conventional analgesia with cyclooxygenase−2 inhibitors and morphine PCA (Control group). The primary outcome was morphine consumption in the first 24 h after surgery. Secondary outcomes were pain scores, nausea, vomiting, time to ambulation and flatus, length of hospital stay, satisfaction score, the 40-item Quality of Recovery score (QoR-40) and the Short-Form Health Survey (SF-36) scale. Results Morphine consumption in the first 24 h was 6 (3–9.8) mg in the Study group and 7 (3.5–12.5) mg in the Control group (p = 0.222). The Study group showed lower morphine consumption up to 6 h, lower pain scores up to 48 h, and earlier time to ambulation and flatus. The global QoR-40 score at 48 h [182 (173–195) vs. 173.5 (154–185.5), p = 0.024], subdimension scores of physical dependence at 24 h, physical comfort and pain at 48 h were significantly improved in the Study group. Conclusion Preemptive multimodal analgesia was not superior to conventional analgesia in reducing 24 h morphine consumption; however, it showed a significantly improved pain control and early quality of recovery thus can be recommended for gynecologic oncology patients undergoing laparotomy.